Impact of Air Pollution on the Long-Term Decline of Non-Idiopathic Pulmonary Fibrosis Interstitial Lung Disease - Pablo Mariscal-Aguilar; Luis Gómez-Carrera; Gema Bonilla; Carlos Carpio; Ester Zamarrón; María Fernández-Velilla; Mariana Díaz-Almirón; Francisco Gayá; Elena Villamañán; Concepción Prados; Rodolfo Álvarez-Sala (Atmosphere)
Objective: This study examines the association between major urban pollutants and the long-term decline of non-idiopathic pulmonary fibrosis interstitial lung disease [non-IPF ILD]. Materials and methods: A total of 41 patients with non-IPF ILD were analyzed from 2011 to 2020, correlating disease long-term decline with concentrations of key pollutants [SO2, CO, NO2, O3, PM2.5, and PM10] in Madrid. The likelihood of meeting severity criteria was assessed using a generalized linear model, considering the average pollutant levels during severe episodes. Results: At diagnosis, the average age of patients was 62.95 ± 13.13 years, with 47.6% women. The study found no significant association between pollution levels and the probability of meeting severity criteria for non-IPF ILD. The odds ratios were as follows: OR SO2 = 0.92 [0.82–1.03], p = 0.16; OR CO = 0.99 [0.97–1.05], p = 0.70; OR NO2 = 0.97 [0.92–1.03], p = 0.38; OR PM2.5 = 0.79 [0.54–1.17], p = 0.24; OR PM10 = 1.1 [0.94–1.28], p = 0.21; OR O3 = 0.97 [0.92–1.01], p = 0.20. Conclusions: Our study suggests that, within the cohort of 41 patients with non-IPF ILD enrolled in this study, urban air pollutants in Madrid are not significantly linked to increased long-term decline of non-IPF ILD. This is one of the first studies to explore the impact of various urban pollutants on a diverse cohort of non-IPF ILD patients, including rare conditions like LAM and histiocytosis X. Further research with larger sample sizes and comprehensive exposure assessments is recommended.